Rad der Zeit . Wheel of Time - Herzog, Werner (Germany, 2003)
Duration: 01:21:00 Documentary on the pilgrimage to the holy Tibetan mountain of Kailas. In 2002, half a million pilgrims gathered in Bodh Gaya, India to promote universal peace and harmony on the occasion of one of the most important Tibetan Buddhist rituals, Kalachakra. An impassioned philosophical discussion under the tree where Buddha achieved enlightenment, preparation of food for the never-ending crowds of believers, an interview with the Dalai Lama, and the first footage of these secret Buddhist ceremonies are all part of Werner Herzog‘s film, offering spiritual insight into contemporary Tibetan Buddhism.